A cluster analysis of high-performance female team players` perceived motivational climate: Implications on perceived motor competence and autonomous behaviour - AbraldeJ. A.; Marin, L. C.; Manzano-Sanch; Manzano-Sánchez, D.; Gomez Lopez, M.; Sánchez-Alcaraz, B. J. (PLOS ONE, 2022)
High performance sport for females is an area which is gaining more and more relevance today, but which hasn`t received the same research interest as sport for males. The aim of the present study was to analyse the motivational climate perceived by high performance female athletes and the implications on perceived motor competence and autonomous behaviour and check the differences according category, sport experience and training hours in performance and master climate. The participants were 615 female athletes who practice top level team sports, with ages comprised of 16 to 38 (M = 22,10; SD = 4,91). The sample consisted of two different categories: junior (n = 242) and senior (n = 373). These players participated in different team sports, specifically football, handball, basketball and volleyball, training between 6 and 24 hours a week (M = 8,34; DT = 4,33). The variables measured were: perceived motivational climate in sport, autonomous behaviour and perceived motor competence. A cluster analysis was carried out using, as a variable, the perceived motivational climate, and showing the existence of two profiles, one related to ego and the other to task. The multivariate analysis showed that the profile orientated towards the task had significant differences compared to the autonomous behaviour (M = 4.66 vs M = 3.41). At the same time an analysis was carried out looking at different social demographic variables, revealing how there were differences in the sports experience (those participants with more than ten years` experience were more orientated towards ego, compared to those with less than ten years` experience) and the category (junior athletes were more orientated towards the task, compared to senior athletes). It was concluded that a greater orientation towards the task can lead to an improvement in the perception of motor competence, with the youngest and least experienced athletes being the most prominent in this category.